Peningkatan Gerakan Berhenti Merokok untuk Mendukung Gerakan Masyarakat Hidup Sehat (GERMAS) - Hiola, Tumartony Thaib; Ali, Indra Haryanto; Mahdang, Putri Ayuningtias; Mustafa, Yanti (Universitas Nusantara PGRI Kediri, 2021)
World Health Organization (WHO) states that cigarette smoke environment is the cause of various diseases, in active and passive smokers. Health problems that arise at this time are the result of unhealthy behavior, this can be prevented if the focus is on health efforts for family and community independence to have a clean and healthy lifestyle (PHBS). One of the breakthroughs is through the Community Healthy Life Movement (GERMAS). The purpose of this community service is to provide education and socialization of the Stop Smoking Movement to Support the Community Healthy Life Movement (GERMAS) in Pauwo Village. The method of implementation is: visiting houses where active smokers are present, then conducting a pre-test as initial data to determine public understanding of the dangers of smoking and the importance of clean and healthy living habits; After that, education and leaflets that are designed as attractive as possible are given so that people are interested in reading them. Leaflets contain information about the dangers of smoking, tips on quitting smoking and the importance of implementing PHBS; and finally, an evaluation was carried out using a post-test questionnaire. The results of the activity show that there is an increase in people's understanding of the dangers of smoking and the importance of implementing PHBS in everyday life. The conclusion of this community service is that the community's understanding of smoking and the importance of implementing PHBS in life to support the GERMAS program has increased.